The Light We Carry : Overcoming in Uncertain Times - Obama, Michelle (New York : Crown, 2022)
"Mrs. Obama offers readers a series of fresh stories and insightful reflections on change, challenge, and power, including her belief that when we light up for others, we can illuminate the richness and potential of the world around us, discovering deeper truths and new pathways for progress. Drawing from her experiences as a mother, daughter, spouse, friend, and First Lady, she shares the habits and principles she has developed to successfully adapt to change and overcome various obstacles--the earned wisdom that helps her continue to 'become.' She details her most valuable practices, like 'starting kind,' 'going high,' and assembling a 'kitchen table' of trusted friends and mentors. With trademark humor, candor, and compassion, she also explores issues connected to race, gender, and visibility, encouraging readers to work through fear, find strength in community, and live with boldness"--Provided by publisher.
The power of small -- Decoding fear -- Starting kind -- Am I seen? -- My kitchen table -- Partnering well -- Meet my mom -- The whole of us -- The armor we wear -- Going high.
Includes bibliographical references (pages 309-316).
Keywords: Presidents' spouses -- United States; African American women lawyers -- Illinois -- Chicago -- Biography; Lawyers -- Illinois -- Chicago -- Biography; Conduct of life